2020
DOI: 10.1002/jhet.3961
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic carbon nanotube as a highly stable and retrievable support for the heterogenization of sulfonic acid and its application in the synthesis of 2‐(1H‐tetrazole‐5‐yl) acrylonitrile derivatives

Abstract: In the present study, a novel magnetic carbon nanotube functionalized by chlorosulfonicacid (Fe3O4‐CNT‐SO3H) with nanotube morphology decorated by the spherical nanoparticles was prepared, characterized and introduced as a retrievable magnetic heterogeneous nanocatalyst for green synthesis a variety of 2‐(1H‐tetrazole‐5‐yl) acrylonitrile via multicomponent domino Knoevenagel condensation/ 1,3‐dipolar cycloaddition reaction between aromatic aldehydes, malononitrile, and sodium azide under solvent free condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The Fe 3 O 4 @BNPs-CPTMS-chitosan-Pd(0) offered numerous advantages such as green ligand (Chitosan), thermal and mechanical stability, high-grade magnetic strength, high surface area, reusability (5 cycles), an easy and fast separation. 65 Akbarzadeh et al embedded chlorosulfonic acid functionalized carbon nanotubes on Fe 3 O 4 nanoparticles to produce 66 Similarly, it was found that, unmodied nano Fe 3 O 4 exhibited remarkable catalytic activity for 5-substituted tetrazole synthesis from malononitrile (1 mmol), aromatic aldehyde (1 mmol), sodium azide (1 mmol) as tabulated in Table 4, entry 4. They observed that nano Fe 3 O 4 gave best result at 20 mol% amount.…”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fe 3 O 4 @BNPs-CPTMS-chitosan-Pd(0) offered numerous advantages such as green ligand (Chitosan), thermal and mechanical stability, high-grade magnetic strength, high surface area, reusability (5 cycles), an easy and fast separation. 65 Akbarzadeh et al embedded chlorosulfonic acid functionalized carbon nanotubes on Fe 3 O 4 nanoparticles to produce 66 Similarly, it was found that, unmodied nano Fe 3 O 4 exhibited remarkable catalytic activity for 5-substituted tetrazole synthesis from malononitrile (1 mmol), aromatic aldehyde (1 mmol), sodium azide (1 mmol) as tabulated in Table 4, entry 4. They observed that nano Fe 3 O 4 gave best result at 20 mol% amount.…”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
“…Development of copper-based nanomaterials received huge attention in recent years specially in domain of nano-catalysis organic transformations due to its extensive range of oxidation states which can enables reactivity through both one-and two-electron pathways. 66 Also, copper-based nano-materials found applications in various other areas like nanotechnology, electrocatalysis, and photocatalysis. [68][69][70] In this context, Cu-immobilized heterogenous nano-catalysts have been extensively utilized in synthesis of tetrazoles derivatives (Tables 5-8).…”
Section: Copper-based Nanomaterials Catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] This paper is a continuation of previous researches on the synthesis and application of new green separable heterogeneous catalysts. [39][40][41][42][43][44] This report shows our efforts to make a novel palladium catalyst using both nitrogendoped carbon materials prepared by hydrothermal carbonization process and as-prepared magnetic Fe 3 O 4 as a support. This combination offers benefits of simple separation, great reusability, and perfect ability to load a considerable amount of palladium.…”
Section: Introductionmentioning
confidence: 99%